PENGELOLAAN DAYA TARIK WISATA BERBASIS MASYARAKAT DI DESA PECATU, KUTA SELATAN, KABUPATEN BADUNG - Yudasuara, I Ketut (Jurnal Master Pariwisata (JUMPA), 2015)
This study analyzes the tourist attraction management by PecatuVillage, South Kuta, Badung Regency. Through the regulation20/1994 concerning the Management and Retribution of TouristObject to manage the Uluwatu Temple outer area as a touristattraction, Badung Regency Goverment gave license to PecatuVillage to manage those attractions. The purpose of this researchis to find out the form, the obstructions and the efforts of DesaPakraman Pecatu in term of tourism attraction management.Theories utilized in this study included functionalism theory,structuration theory, and the theory of hegemony. The studyshows that tourist attraction outside area of Uluwatu Temple ismanaged directly by Desa Pakraman Pecatu, while other touristattractions managed by the community in the respected areaof the attractions. There are several obstructions that faced bymanagement of tourist attractions, such as limited of humanresources, limited of facilities, and limited of fund, lack ofmanagement regulation, inter-organizational coordination, andproperty ownership. The efforts which have been done to solvethe problem such as, the establishment of tourist attractionmanagement, the restructurization of tourist attraction, thepreparation of the management and retribution regulations, theempowerment of the society, and the improvement of interorganizationalcooperation.
Keywords: management, tourist attraction, Uluwatu Temple, community based tourism.